2021
DOI: 10.1595/205651321x16013966874707
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Iridium-Based Catalysts for Acidic Water Electrolysis: A Minireview of Wet-Chemistry Synthesis Methods

Abstract: With the increasing demand for clean hydrogen production, both as a fuel and an indispensable reagent for chemical industries, acidic water electrolysis has attracted considerable attention in academic and industrial research. Iridium is a well-accepted active and corrosion-resistant component of catalysts for oxygen evolution reaction (OER). However, its scarcity demands breakthroughs in catalyst preparation technologies to ensure its most efficient utilization. This minireview focusses on the wet-chemistry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Higher crystallinity of IrO 2 increases its electrochemical stability but also dampens activity. [ 19,21 ] The chosen temperature at 375 °C, as suggested by Böhm et al., does seem to invoke the majority of Ir oxidation, while preserving low crystallinity of IrO 2 , improving its electrochemical activity, and preserving disperse small particles to improve activity even further. [ 8 ] Trends observed in the high‐temperature diffractograms can also be seen in thermally treated catalysts, with Ir(111) narrowing and the emergence of IrO 2 reflexes in calcined RS catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher crystallinity of IrO 2 increases its electrochemical stability but also dampens activity. [ 19,21 ] The chosen temperature at 375 °C, as suggested by Böhm et al., does seem to invoke the majority of Ir oxidation, while preserving low crystallinity of IrO 2 , improving its electrochemical activity, and preserving disperse small particles to improve activity even further. [ 8 ] Trends observed in the high‐temperature diffractograms can also be seen in thermally treated catalysts, with Ir(111) narrowing and the emergence of IrO 2 reflexes in calcined RS catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…With MAF employing a salt melt using only readily available NaNO 3 , this method can be easily adapted to industrial processes. [ 19 ] Catalyst properties like particle size and crystallinity are also easily modifiable by temperature variation. In contrast, the other methods employ a wet chemical approach that can increase complexity and may require the substitution of solvents or additives at high scales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Many efforts have been devoted to developing advanced Irbased catalysts and searching the key factors related to OER performance at Ir sites by precise structural characterizations and sophisticated theoretical calculations. Natalia et al, 7 Duan et al, 8,9 Wang et al 10 and Zhao et al 11 summarized in detail the recent progress of Ir-based catalysts and also gave meaningful guidance for subsequent studies. Moreover, Camila et al 12 had done quantitative benchmarking work on IrO x to deduce a selection of suitable catalysts for diminishing the cost of PEM; Marion et al 13 based on amorphous IrO x revealed that surface structural features have a greater effect on OER activity than the iridium oxidation state.…”
Section: Introductionmentioning
confidence: 99%